1991
DOI: 10.1104/pp.96.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, Developmental, and Genetic Factors that Modulate the Agrobacterium-Vitis Interaction

Abstract: Tumor formation in Vitis species and hybrids, incited by Agrobacterium tumefaciens, was altered by chemical, physical, developmental, and genetic variables. Knowledge of the effect of these variables was used to develop a stringent in vitro assay system to select parents for a study of genetic factors that modulate tumor formation. Tumor formation was reduced by short day preconditioning of assay plants and by inoculation of the morphological apex of isolated stem segments. Pretreatment of plants with auxin or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Even within a species, different cultivars or ecotypes may show different degrees of susceptibility to tumorigenesis by particular Agrobacterium strains. These differences have been noted in maize (Ritchie et al 1993), various legumes (Hood et al 1987, Owens andCress 1984), aspen (Beneddra et al 1996), pine (Bergmann and Stomp 1992), tomato (Van Roekel et al 1993), Arabidopsis (Nam et al 1997) and grape (Lowe and Krul 1991). The ability of particular Agrobacterium strains to transform plant cells is defined by mechanisms necessary for attachment and DNA-transfer, and the ability of plants to produce different inducer molecules.…”
Section: Plant Species and Genotypementioning
confidence: 92%
“…Even within a species, different cultivars or ecotypes may show different degrees of susceptibility to tumorigenesis by particular Agrobacterium strains. These differences have been noted in maize (Ritchie et al 1993), various legumes (Hood et al 1987, Owens andCress 1984), aspen (Beneddra et al 1996), pine (Bergmann and Stomp 1992), tomato (Van Roekel et al 1993), Arabidopsis (Nam et al 1997) and grape (Lowe and Krul 1991). The ability of particular Agrobacterium strains to transform plant cells is defined by mechanisms necessary for attachment and DNA-transfer, and the ability of plants to produce different inducer molecules.…”
Section: Plant Species and Genotypementioning
confidence: 92%
“…Genetic analysis of crosses between susceptible cultivars/ecotypes and resistant cultivars/ecotypes indicated that the phenotype was transmitted to progenies as a heritable trait controlled by dominant (Szegedi and Kozma 1984;Lowe and Krul 1991), recessive (Mauro et al 1995) or semidominant genes (Nam et al 1997). The inheritance of these traits are determined by a single gene or a single major contributing locus (Szegedi and Kozma 1984;Nam et al 1997), or by quantitative trait loci (Bailey et al 1994).…”
Section: Introductionmentioning
confidence: 97%
“…It has long been noted that different species (Anderson and Moore 1979) and cultivars of the same species may differ remarkably in their susceptibility to Agrobacterium infection (Nam et al 1997;Bailey et al 1994;Lowe and Krul 1991;Smarrelli et al 1986). Genetic analysis of crosses between susceptible cultivars/ecotypes and resistant cultivars/ecotypes indicated that the phenotype was transmitted to progenies as a heritable trait controlled by dominant (Szegedi and Kozma 1984;Lowe and Krul 1991), recessive (Mauro et al 1995) or semidominant genes (Nam et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…have been noted in rice [57], maize [58], various legumes [55], aspen [56], cucurbits [59], Pinus species [60], tomato [61], Arabidopsis [62], grape [63], and other species. Although some differences in transformation frequency may be attributed to environmental or physiological factors, a genetic basis for susceptibility has clearly been established in a few plant species [62,[64][65][66].…”
Section: Current Progress In Biological Research 374mentioning
confidence: 99%